Pengaruh Pemberian Beberapa Bakteri Terhadap Kelangsungan Hidup Benih Ikan Lele Dumbo (Clarias sp.) [The Effect Of Bacteria Supply To Survival Rate Juvenile Of African Catfish (Clarias sp.) ] - Muhammad Arief; Irene Puspitasari; Rahayu Kusdarwati (Faculty of Fisheries and Marine Universitas Airlangga, 2010)
Abstract Commodities African catfish (Clarias sp) is a rapidly growing commodity in Indonesia. Clarias gariepinus is one of the leading commodities and have a good market. African catfish hatchery fish is generally done in areas that have abundant water resources so that a minimal constraint on the area of water. Therefore applied a closed system with the addition of bacteria recirculation degrading organic material that is expected to reduce the accumulation of organic material, there by increasing the survival of African catfish fry. This study aimed to investigate the influence of bacteria that degrade organic material in a closed recirculation system on the survival of fish fry of African catfish (Clarias sp.). This research using Completely Randomized Design with four treatments and five replications of each K treatment (0%), A (1%) (6.0x108 CFU / ml), B (3%) (1.8x109 CFU / ml ) and C (5%) (3.0x109). added bacteria consisting of Pseudomonas pseudomallei with similarity index (97.81%), Pseudomonas stutzeri with similarity index (97.81%), Pseudomonas stutzeri with similarity index ( 61.21%) The results of this study indicate that the addition of Pseudomonas pseudomallei (97.81%), Pseudomonas stutzeri (97.81%) and Pseudomonas stutzeri (61.21%) gave significant differences (p <0.05) against survival of fish fry of African catfish.